Building National Consciousness in Primary School Students through English Language Teaching - Thinless, Padma; Rankawat, Devendra (THE PRIMARY TEACHER, 2019)
Being ‘conscious of’ something means being aware of one’s environs. National consciousness is not a tangible thing; yet, it plays an important role in nationbuilding. It plays a crucial role in promoting national unity, peace, diversity, patriotism, and gives a sense of belonging within the diverse national community. The concept of ‘nation’ is an artificial one; therefore it requires a conscious effort to inculcate the right values and attitudes in children so that they may grow into proud citizens tomorrow. National consciousness refers to a state of awareness of one’s surrounding as well as the necessary sense of shared identity, unity, and bonding among the people of a particular nation. Since the nation rests on the idea of a continuous history, bringing up children on the diet of national history would likely result in a better future for children. This paper is an attempt to find out whether the primary school English language curriculum addresses the issue of national consciousness. In this direction the study seeks to analyse whether the content and style of representation in the Marigold English textbooks instils national consciousness and if yes, to what extent. Also, whether there can be further reinforcement of this idea in verbal and visual content of the books.